TRIPs Agreement : a guide for the South : the Uruguay Round Agreement on Trade-Related Intellectual Rights (South Centre GenevaCH, 1997)
Presents an overview of the Agreement on Trade-Related Intellectual Property Rights (TRIPs), which was negotiated as an integral part of the Uruguay Round.
Bibliography: 87-92 p.